2019
DOI: 10.1007/jhep03(2019)027
|View full text |Cite
|
Sign up to set email alerts
|

(0,4) brane box models

Abstract: Two-dimensional N = (0, 4) supersymmetric quiver gauge theories are realized as D3-brane box configurations (two dimensional intervals) which are bounded by NS5-branes and intersect with D5-branes. The periodic brane configuration is mapped to D1-D5-D5 brane system at orbifold singularity via T-duality. The matter content and interactions are encoded by the N = (0, 4) quiver diagrams which are determined by the brane configurations. The Abelian gauge anomaly cancellation indicates the presence of Fermi multipl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 40 publications
0
73
0
Order By: Relevance
“…We computed Page charges and put them in correspondence with the putative colour and flavour branes in the Hanany-Witten set-ups associated to our SCFTs. The CFTs are defined as the IR limit of UV well-behaved long quivers with (0, 4) SUSY, that generalise 2-d (0,4) quivers previously discussed in the literature -see [40,48]. After presenting our proposed duality we discussed a number of examples of increasing complexity that together constitute a stringent test of our proposal.…”
Section: Discussionmentioning
confidence: 99%
“…We computed Page charges and put them in correspondence with the putative colour and flavour branes in the Hanany-Witten set-ups associated to our SCFTs. The CFTs are defined as the IR limit of UV well-behaved long quivers with (0, 4) SUSY, that generalise 2-d (0,4) quivers previously discussed in the literature -see [40,48]. After presenting our proposed duality we discussed a number of examples of increasing complexity that together constitute a stringent test of our proposal.…”
Section: Discussionmentioning
confidence: 99%
“…We define half-indices of 3d N = 4 gauge theories and full-indices of 2d N = (0, 4) gauge theories. In section 3 we study simple examples of brane box models in [35]. We propose the minimal N = (0, 4) mirror symmetry by computing the indices.…”
Section: Structurementioning
confidence: 99%
“…In this section, we analyze simple examples of N = (0, 4) brane box models in [35]. In particular, we propose simple N = (0, 4) mirror symmetry that may be related to the 3d N = 4 mirror symmetry between 3d SQED 1 and free twisted hypermultiplet [62].…”
Section: N = (0 4) Box Modelsmentioning
confidence: 99%
“…Non-compact D4 branes provide the necessary flavour groups that render the nodes associated to the new, colour, D6 branes non-anomalous. Our quivers also generalise the (0,4) quivers constructed in [32] from D3-brane box configurations to gauge nodes with different gauge groups. 8 -BPS brane set-ups such as the one depicted in table 1 were discussed in [7] in the context of 2d defect CFTs originating from D2-D4 branes living in 6d (1,0) CFTs.…”
mentioning
confidence: 95%
“…They also play a prominent role in the description of self-dual strings in 6d (1,0) CFTs realised in M-and F-theory [23][24][25][26][27][28]. Their extensions to 2d (0,4) CFTs with large superconformal algebra have also received a good deal of attention [29][30][31][32][33]. Very recently we have also shown that they can be realised in larger D2-D4-D6-NS5-D8 brane systems [34,35].…”
Section: Introductionmentioning
confidence: 99%